1996
DOI: 10.1007/s002800050535
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic studies of 13- cis -retinoic acid in pediatric patients with neuroblastoma following bone marrow transplantation

Abstract: A phase I clinical trial of 13-cis-retinoic acid (cis-RA) was undertaken to determine the maximally tolerated dose (MTD) and pharmacokinetics (PK) of cis-RA following bone marrow transplantation (BMT) in children with high-risk neuroblastoma. Mean peak serum levels of cis-RA in 31 pediatric patients ranged from 4.9 to 8.9 microM following doses of 100-200 mg/m2 per day, divided into two doses every 12 h administered orally. The PK of cis-RA obeyed a single-compartment model following first-order absorption in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
2
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 20 publications
2
43
2
1
Order By: Relevance
“…It is notable that the plasma concentrations achieved in the current study are up to four-fold lower than those reported in a phase I study of the same formulation (Khan et al, 1996). The reasons for this difference are not easily identified.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…It is notable that the plasma concentrations achieved in the current study are up to four-fold lower than those reported in a phase I study of the same formulation (Khan et al, 1996). The reasons for this difference are not easily identified.…”
Section: Discussioncontrasting
confidence: 80%
“…Analysis of patient samples from a phase I study of 13-cisRA previously suggested increasing levels of the metabolite 4-oxo-13-cisRA during a course of treatment, although actual concentrations were not quantified (Khan et al, 1996).…”
mentioning
confidence: 99%
“…61 Based on observations that RA can also induce differentiation of neuroblastoma cell lines in vitro, 16 -18 RA has been used for several clinical trials in neuroblastoma patients with variable results. [37][38][39][40] However, a recent study using high-dose 13-cis RA treatment after myeloablative therapy and autologous bone marrow transplantation showed encouraging results. 41 Since differentiation and/or growth arrest induced by RA, TPA or vitamin D 3 was shown to be potentiated by IFN-␥ in several cell types, [42][43][44][45][46][47] the aim of our investigation was to determine whether IFN-␥ would synergize with RA or TPA to induce differentiation and growth inhibition in neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our results together with those of Wuarin et al 50 and a publication by Cornaglia et al, 48 reporting that combined therapy with RA and IFN-␥ inhibited tumor formation of LA-N-5 cells injected in nude mice, suggest that RA and IFN-␥ in combination may be of therapeutical interest. Presently both RA [37][38][39][40] and IFN-␥ 62 have been used as single agents in clinical trials for cancer therapy. This is a good basis for combination therapy with the 2 agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation